INTEGRAÇÃO LATINO-AMERICANA E CONSCIÊNCIA HISTÓRICA: A noção de pertencimento latino-americano de jovens brasileiros no ano de 2013 - Barom, Wilian Carlos Cipriani (2017)
The present thesis summarizes the results of an investigation into the possibility of A feeling of belonging of 2240 young Brazilians to Latin America - and its manifestations in varying degrees, made from selected questions of the project young people and History. In the first chapter, the research was contextualized from a reflection on the phenomenon of political regionalism, the current blocks that compose and proposes the integration and how, in their official regulations, request regional identity and common to the region. In the third, there was a brief recovery in the history of the Young project and the story in Brazil, a reflection on the chosen collection method of and systematization of data – the Software GNU PSPP-, and analysis of the six questions chosen of the project, from the variables geographic location, socioeconomic condition and types of cities, which are linked, directly or indirectly the issue of regional belonging. Among the conclusions of the thesis are: the prevalence of positioning indifferent in the responses of young people; the presence of the (neo) liberal ideology and ethical-moral criteria as axes that structure the interpretation of reality, in parallel to recoveries of memories and experiences from the past; the presence of notions of belonging, which varied according to the issues and variables; a patriotic feeling which is not translated by the young people's interest on the history of the country, the of development of Nations, democracy, in the knowledge of the region itself, the of place where lives and the of history of ordinary people; significant interest in the flow of products, work and study in the region, in the unification of the currency and the construction of infrastructure which benefit the commercial integration between the South American countries; and, yet, the significant rejection on the part of young people to the idea of a common, unified, future for the region.